Analisis Peramalan Permintaan pada Divisi Welding di PT Terang Dunia Internusa dengan Menggunakan Metode Single Moving Average - Kusuma, Harun Indra; Darmono, Bambang; Mahera, Liza; Aulia, Dita; Irsyadi, Muhammad Tegar; Sasmita, Muhammad Zeinny Hasbunallah; Novalia, Femy (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The bicycle manufacturing industry is a sector that continues to experience growth as public awareness of the importance of a healthy, environmentally friendly lifestyle increases, and interest in cycling grows. In the production process, the Welding Division plays a crucial role as it is responsible for assembling the main components of bicycles, namely the frame. This study focuses on demand forecasting in this division so that the company can determine production targets more accurately. The single moving average method was chosen as the forecasting technique because it is suitable for limited data conditions, both for production and sales needs. The researchers divided this method into three variations: forecasting with a 2-month, 3-month, and 4-month period. The analysis results showed that the 2-month single moving average method provided the most accurate results with a mean absolute percentage error of 28%, which is lower than the other methods. Overall, the average production in the Welding Division reached 54,050 units.